Airborne Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): What We Know. (18th January 2021) - Samet, Jonathan M; Prather, Kimberly; Benjamin, Georges; Lakdawala, Seema; Lowe, John-Martin; Reingold, Arthur; Volckens, John; Marr, Linsey C
Abstract: We examine airborne transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) potential using a source-to-dose framework beginning with generation of virus-containing droplets and aerosols and ending with virus deposition in the respiratory tract of susceptible individuals. By addressing 4 critical questions, we identify both gaps in addressing 4 critical questions with answers having policy implications.